(untitled) (Revista de Psicología, 2020)
Introduction: bullying is an important risk factor for the mental health of adolescents. Purpose: the present research studied the definitions and level of bullying in adolescents. Sample: a sample constituted of 202 adolescents in Paraná, Argentina. Measures: Smith’s Cartoons Task, Vaillancourt’s open question, and Olweus questionnaire to measure bullying. Results: only 8% indicated the imbalance of force, 4%, repetition and 10%, intentionality. In Smith’s task, the vast majority could identify bullying vignettes, but they also included situations that were not harassment such as bullying. Conclusion: definitions of what is bullying given by adolescents only partially coincide with the scientific definition of such behavior.